(untitled) (Tanzania Medical Journal, 2017)
Background: Guidelines for the treatment of HIV recommend the use of immunological and clinical criteria for treatment monitoring in resource limited settings. Data on the magnitude of immunological treatment failure in sub-Saharan Africa is scarce. This study aimed at assessing the magnitude and factors associated with immunological failure among HIV infected patients on HAART.Methods: A cross sectional study was conducted at Bugando Medical centre HIV care and treatment centre between February-July 2011, involving HIV-infected patients on first line ART for at least one year. Patients with concurrent infections and critically ill were excluded. A designed questionnaire was used to collect socio-demographic and clinical data of patients. Continuous variables were summarized by median and interquartile ranges (IQRs) and categorical variables were summarized by frequency and percentage. Logistic regression was used to find the predictors of immunological failure.Results: A total of 274 participants were enrolled for this study. The median duration on ART was 26 months (IQR 12-45). Majority of the participants were female (65.7%); the baseline CD4 count was 139.5 cells/ul (IQR 60-210). Most of the study participants (47.8%) presented with WHO clinical stage 3 at the time of enrollment to the clinic. Out of the 274 study participants, 57% fulfilled the criteria for immunological failure. WHO clinical stage 3 or 4 at ART initiation (p<0.001), low level of reported adherence (p=0.001) and longer duration on ART (p<0.001) were predictors of immunological failure in this cohort.Conclusion: Immunological treatment failure was very high in this cohort of HIV-infected patients on first line ART. WHO clinical stage 3 or 4 at enrollment, low level of adherence and longer duration on ART were predictors of immunological failure.